2020
DOI: 10.1200/cci.20.00023
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wearable Activity Tracker in Patients With Cancer Undergoing Chemotherapy: Toward Evaluating Risk of Unplanned Health Care Encounters

Abstract: PURPOSE Unplanned health care encounters (UHEs) such as emergency room visits can occur commonly during cancer chemotherapy treatments. Patients at an increased risk of UHEs are typically identified by clinicians using performance status (PS) assessments based on a descriptive scale, such as the Eastern Cooperative Oncology Group (ECOG) scale. Such assessments can be bias prone, resulting in PS score disagreements between assessors. We therefore propose to evaluate PS using physical activity measurements (eg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The studies included in this review article employed different interventional approaches to improve the clinical outcomes of the participants. Most of the studies used a mobile application to provide the intervention [ 22 , 34 , 35 , 39 , 40 , 46 , 53 , 54 , 57 ]. Of the 38 studies, 3 provided the intervention by sending text messages [ 22 , 45 , 57 ], and 4 conducted a general group session or included a virtual support group [ 39 , 41 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in this review article employed different interventional approaches to improve the clinical outcomes of the participants. Most of the studies used a mobile application to provide the intervention [ 22 , 34 , 35 , 39 , 40 , 46 , 53 , 54 , 57 ]. Of the 38 studies, 3 provided the intervention by sending text messages [ 22 , 45 , 57 ], and 4 conducted a general group session or included a virtual support group [ 39 , 41 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average adherence percentage was calculated for each segment. The intervention-based segments included studies with weeks 1 [ 48 , 49 ], 2 [ 27 , 55 ], 3 [ 50 , 52 , 57 ], 4 [ 36 , 37 , 53 ], 7 [ 28 ], 8 [ 32 , 33 , 34 ], 10 [ 24 , 30 , 41 ], 12 [ 20 , 21 , 23 , 25 , 26 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 56 ], 17 [ 29 ], 24 [ 22 , 31 ] and 43 [ 35 ]. In the graph, (1.84) indicates the studies grouped in this segment that had a one-week intervention with an average adherence of 84%.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, studies examining the applicability of objective activity evaluation, such as measurements by wearable technology, are being conducted to investigate the usability of activity data for survival prediction. While several studies have identified associations between activity data of cancer patients and their clinical outcomes, such as unplanned healthcare encounters ( 38 ), adverse events, hospitalizations, and survival ( 25 ), no previous studies have utilized the activity data to build a prediction model that suggests survival outcomes. To our knowledge, this is the first study that applied objective activity data of patients in a deep-learning model to provide survival outcome predictions in the end-stage cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of wearable technology have been less promising when analyzing step counts. Nilanon et al 10 studied the use of an activity tracker in patients receiving outpatient chemotherapy, and only 68% of all patients were compliant with wearing the device, and there was no correlation between step counts and unplanned health encounters. However, these authors did find a significant correlation between fewer nonsedentary hours and a reduced incidence of health encounters, suggesting that impaired activity level is associated with increased care utilization.…”
Section: Discussionmentioning
confidence: 99%